AN ANALYSIS OF TABOO WORDS IN THE MOVIE ‘SCORSESE CASINO’ - GRACE ROTUA SIMANJUNTAK; FAUZIAH KHAIRANI LUBIS (LINGUISTICA, 2022)
In social interactions, there are still many people who use taboo words to mock and even berate others. It maes communication not good, so that it can cause conflict between each other. In this study we will discuss about the taboo words used by the characters in the Scorsese's Casino film. The purpose of this study was to find out the types of taboo words contained in Scorsese's Casino Movie, to eliminate the taboo words and the reasons why these taboo words were spoken. 2006). This study used descriptive qualitative method. The data in this study is from Film Casino which contains the translation of taboo words and the reasons why taboo words are spoken. Data were collected in the form of sentences containing taboo words. There are 68 data found in this study, here are the results of the analysis. There are four types of taboo words found in Scorsese's Casino, namely epithets, profanity, vulgarity, and obscenity. There are four reasons why taboo words are spoken which are to draw attention to oneself, to show contempt, to be provocative. Based on the results above, it can be seen that most of the characters in Scorsese's Casino use epithets and obscenity to insult, these two types of words are the most influential words. While the reason why taboo words are spoken is dominantly to show contempt. So this research is useful for the community so that people can take better care of their words in communicating by using better words.